MENEROPONG DETERMINAN OPINI LKPD KABUPATEN/KOTA DI SUMATERA UTARA - Muhammad Iqbal Alal Maula; Puji Wibowo (Center for Economic Studies Universitas Katolik Parahyangan, 2022)
The financial reports of lower level governments in North Sumatra Province still require serious attention because there are several regions that have not yet obtained unqualified opinions. This study aims to analyze the factors that influence BPK's audit opinion on those financial statements. This research observes financial reports and reports on the results of BPK audits during the 2016-2018 period. The sample selection method was purposive sampling and obtained 31 districts / cities. The panel data analysis used in this research is the random-effect model. Based on the results of statistical tests, the number of audit findings is proven to have a negative impact on the quality of financial reports. Meanwhile, the level of financial statement disclosure and regional characteristics cannot explain the variation in audit opinion between regions.